The Influence of Leverage on Accounting Policy and Reporting Choices (gjstudies, 2022)
This research investigates the underexplored nexus between corporate financial leverage andthe selection of accounting policies and reporting frameworks, moving beyond traditional earnings management perspectives. We propose a novel theoretical framework that conceptualizesaccounting policy choice as a strategic signaling mechanism in high-leverage environments,where firms face heightened scrutiny from debt holders and capital markets. Through a mixedmethods approach combining computational text analysis of financial statement narratives witha proprietary dataset of firm-level accounting policy elections, we examine how leverage ratiosinfluence the adoption of specific accounting standards, disclosure granularity, and reportingconservatism. Our methodology introduces a ’Leverage-Induced Reporting Pressure’ (LIRP)index, which quantifies the intensity of reporting adjustments attributable to debt levels. Results from a sample of 1,250 publicly traded firms over a ten-year period reveal that highlyleveraged firms are significantly more likely to adopt income-smoothing accounting policies, increase footnote disclosures related to debt covenants and risk, and exhibit a pronounced shifttoward conservative asset valuation methods. Crucially, we identify a non-linear relationship:moderate increases in leverage prompt greater reporting transparency, while extreme leverageleads to obfuscation in specific, complex liability disclosures. The findings challenge the monolithic view of debt as a driver of opportunistic earnings manipulation, instead presenting a morenuanced picture where leverage acts as a catalyst for a comprehensive, and often more rigorous,recalibration of a firm’s entire financial reporting philosophy. This research contributes to accounting theory by integrating capital structure considerations directly into models of financialreporting strategy and offers practical insights for standard-setters, auditors, and credit analystsassessing reporting quality under financial constraint.